Mistaking noise for bias - Blouin, Arthur,Mukand, Sharun W. (CESifo, Center for Economic Studies & Ifo Institute, 2022)
The difficulty in resurrecting inter-ethnic cooperation in the aftermath of violence and genocide is one of the biggest challenges facing post-conflict societies. Using experimental data from post-genocide Rwanda and Burundi, this paper shows that an unwarranted tendency to blame others for negative outcomes is a behavioural barrier that makes reconciliation difficult. We show that individuals systematically (and mistakenly) blame accidental negative shocks (noise) to the deliberate intent of individuals (bias). This
10419/263784
Keywords: Graue Literatur; noise; bias; victim; conflict; reconciliation; attribution